Essay: Transit migrants in Indonesia: Between the devil and the deep blue sea - Missbach, Antje (Pacific Geographies, 2013)
Rahim (not his real name), a young Iraqi man, has been living in transit in Indonesia for more than nine years. Retracing both his journey to the archipelago and his failed attempts to leave again – as his stated intention is to find permanent protection in Australia – frame a difficult time in his life marked by uncertainty, vulnerability and despair. Highlighting Rahim’s destiny sheds light on the general legal and political conditions in Indonesia faced by several thousands asylum seekers and recognised refugees. As many of them cannot return to their conflict-ridden home countries while local integration into the Indonesian society is legally not permitted and resettlement options to safe third countries are only available to very few, they become stuck between “the devil and the deep blue sea”.